2012
DOI: 10.2478/s11532-012-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Flash point of organic binary mixtures containing alcohols: experiment and prediction

Abstract: © Versita Sp. z o.o. Keywords: Flash point • Binary mixture • Pensky-Martens • PredictionUniversity of Chemical Technology and Metallurgy, 1756 Sofia, Bulgaria Mariana Hristova 1* , Dimitar Damgaliev Research ArticleThe flash points of three organic binary mixtures containing alcohols were measured in the present work. The experimental data was obtained using the Pensky-Martens closed cup tester. The experimental data were compared with the values calculated by the Liaw model. Activity coefficients were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
0
12
0
3
Order By: Relevance
“…Some authors have reported the predicted FP for ideal solutions. ,, According to these authors, when the ideal behavior is observed, the mixture FP always present an intermediate value between the most and least flammable compound. As observed in Figure and in Tables –, this is true to the data reported in this study.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some authors have reported the predicted FP for ideal solutions. ,, According to these authors, when the ideal behavior is observed, the mixture FP always present an intermediate value between the most and least flammable compound. As observed in Figure and in Tables –, this is true to the data reported in this study.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The predictive results of applied model describe the experimental data from [2] and [3] well within the error two times lower than experimental one. Based on this evidence, therefore, it appears reasonable to suggest potential application for our model in assessment of fire and explosion hazards, and development of inherently safer designs for chemical processes containing binary mixtures of flammable solvents.…”
Section: Discussionmentioning
confidence: 66%
“…The flash point for a solution can be estimated by Liaw´s model by equation of Le Chatelier [2][3][4] and an extended Antoine equation for estimating the saturated vapor pressure [5] and a model for estimating activity coefficients for given temperature and pressure conditions [6]. The model for predicting the flash point of mixtures take into account the non-ideality of the solution through liquid phase activity coefficients and have been used to predict efficiently the flash point of several mixtures [2,[7][8][9][10][11].…”
Section: Thermodynamic Modelmentioning
confidence: 99%
“…The flash points of pure chemical substances are widely reported in the literature 1,2,5,6 ; however, limited data are available for mixtures because the experimental measurements are relatively expensive and time‐consuming. Therefore, predictive theoretical methods have been studied to estimate the flash point of both pure compounds and mixtures 7 …”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that describe methods to predict the flash point of simple mixtures with well‐defined and controlled characteristics using physicochemical parameters. These methods assume that the mixtures are ideal mixtures and that the liquid phase is in equilibrium with the vapor phase 4,7,8 . However, the calculation based on physicochemical models is not a trivial task, as complex mixtures (such as fragrances) may present large deviations from ideality, where depending on the parameters used, there may be differences in the order of tens 3,7 …”
Section: Introductionmentioning
confidence: 99%